Can a Conical Implant Successfully Address Complex Anatomy in Primary THA? Radiographs and Hip Scores at Early Followup. Issue 2 (February 2016) - Zhang, Quoqiang; Goodman, Stuart B.; Maloney, William J.; Huddleston, James I.
Abstract: Background: Total hip arthroplasty (THA) in patients with small or abnormal proximal femoral anatomy is challenging as a result of complex anatomic deformities in the hip. It is unclear which stem is the most appropriate for these patients. One possible implant design that may help meet this need is the modified Wagner Cone prosthesis, whose design consists of monoblock cone with splines; however, to our knowledge, no clinical results have been published using this implant. Questions/purposes: We evaluated the hip scores and radiographic results (including signs of osseointegration and subsidence) of complex primary THA using the modified Wagner Cone cementless femoral component in patients with small or abnormal proximal femoral anatomic proportions. Methods: Between 2006 and 2011, we performed 59 THAs on patients whose femoral geometry precluded the use of standard‐sized implants. Of these, 49 (83%) received the modified Wagner Cone prosthesis. During this time, our indications for use of the Wagner Cone implant in such patients included: femoral neck retroversion, excessive anteversion of the femoral neck, or small proximal femora not suitable for standard implants. Of those, 40 patients with 49 THAs were available for radiographic and clinical followup at a minimum of 3 years, and no patients were lost to followup. The diagnosis included developmental dysplasia of hip (22 patients, 28 hips), secondary trauma or posttuberculosis osteoarthritis (nine patients, 10 hips), and hip disease secondary to other disorders (eight patients, nine hips) and osteonecrosis (one patients, two hips). Two versions of the stem with 135° (28 hips) or 125° (21 hips) neck angle versions were used to reestablish normal hip biomechanics. Version angle was chosen based on preoperative templating. Cementless cups with screws were used for the acetabulum. Mean followup was 4 years (range, 3‐7 years). Study endpoints were the Harris hip score and radiographic evaluations by a surgeon not involved in the clinical care of the patients (QZ); radiographic analysis included evaluating for the presence or absence of signs of osseointegration (including Engh's criteria) and subsidence. Results: The Harris hip score improved from a mean of 41 ± 9 preoperatively to a mean of 85 ± 10 at last followup (p < 0.01). The mean vertical subsidence was 1.5 ± 1.1 mm. Radiographic evaluation demonstrated stability (no further subsidence) of all implants at last followup. Endosteal spot welds were found in 32 hips (65%). No progressive radiolucencies were observed. One patient (one hip) underwent revision surgery as a result of late infection; no other revisions were performed. Conclusions: The modified Wagner Cone femoral stem has provided improvements in hip scores and promising short‐term radiographic results at short‐term followup in complex cementless THA associated with abnormal or small femoral anatomical proportions in which standard implants are inappropriate. Longer followup will be needed to see if these results endure. Randomized trials are needed to determine the optimal stem design for these patients. Level of Evidence: Level IV, therapeutic study.